Study on the laser crystal thermal compensation of LD end-pumped Nd:YAG 1319 nm/1338 nm dual-wavelength laser. (18th November 2015) - Sun, R; Wu, C T; Yu, M; Yu, K; Wang, C; Jin, G Y
Abstract: The thermal model of laser diode (LD) end-pumped Nd: YAG was established. We analyzed the thermal effect of the crystal during the generation of 1319 nm/1338 nm dual-wavelength laser. Together with the bonded and non-bonded Nd:YAG crystal characteristics, we proposed to consider the bonded crystal's internal temperature distribution of the three axes abc for the first time. The results showed that, compared with the non-bonded crystals, the bonded crystals could effectively reduce the crystal temperature. It provided a theoretical basis to solve the problem related to the thermal effect of the laser crystal and improve the laser output performance. The Nd:YAG laser crystal thermal model in this article could be widely applicable to similar laser crystals. The results provide a method to analyze and evaluate bonding crystal thermal compensation effectiveness by establishing the Nd:YAG crystal's temperature distribution.